THE ROLE OF BAITUL MAL WAT TAMWIL IN COMMUNITY ECONOMIC EMPOWERMENT: A CASE STUDY OF BMT AL MUTHI'IN YOGYAKARTA - Kitara Alvinita, Aisyah; Amalia, Familia Nur; Fairus, Salma (Business Finence Analyst Co.,, 2025)
This study analyzes the role of Baitul Maal Wat Tamwil (BMT) Al-Muthi’in Yogyakarta in empowering the community's economy, especially for Micro, Small, and Medium Enterprises (MSMEs). Using a descriptive qualitative method, this study found that BMT Al-Muthi’in effectively carries out its intermediary function through various financing programs, personal and educational approaches, and sharia-based MSME training. The